Is That West of Us Still the West? A Note on the Humanist Approach to the Question of Continuity vs. Discontinuity (Politeja, 2018)
The article takes up the concept of “Central Eastern Europe” only to show that it makes sense if we can reshape our political imagination. What is crucial is our perception of the West which now is based on intellectual assumptions about the continuity of Western civilization. Rather, we should reflect on the role of discontinuity as the key to contemporary politics or, more broadly, to modernity. To explain this possibility, the Humanists’ (Irving Babbitt’s and Paul Elmer More’s, preceded by Thomas Hulme’s) approach is briefly surveyed, with special reference to the question of civilization vs. barbarism as the most relevant, or most urgent, distinction in the modern world. The main message is that we, the “Central Eastern Europeans,” are very much in need of political realism. This ought to be, however, a type of realism based on profound philosophical insight, like that of the Humanists.